ALDH2 polymorphism, associated with attenuating negative symptoms in patients with schizophrenia treated with add-on dextromethorphan. (October 2015) - Lee, Sheng-Yu; Chen, Shiou-Lan; Chang, Yun-Hsuan; Chen, Po-See; Huang, San-Yuan; Tzeng, Nian-Sheng; Wang, Liang-Jen; Lee, I-Hui; Wang, Tzu-Yun; Chen, Kao-Chin; Yang, Yen-Kuang; Hong, Jau-Shyong; et al.
Abstract: Objective: Increasing the evidence of inflammation's contribution to schizophrenia; using anti-inflammatory or neurotrophic therapeutic agents to see whether they improve schizophrenia treatment. Dextromethorphan (DM), a non-competitive N-methyl-d -aspartate (NMDA) receptor antagonist, might protect monoamine neurons. Whether treating schizophrenia with risperidone plus add-on DM is more effective than risperidone (RISP) alone, and the association between the ALDH2 polymorphism and treatment response were investigated. Methods: A double-blind study in which patients with schizophrenia were randomly assigned to the RISP + DM (60 mg/day; n = 74) or the RISP + Placebo (n = 75) group. The Positive and Negative Syndrome Scale (PANSS) and the Scale for the Assessment of Negative Symptoms (SANS) scores were used to evaluate clinical response during weeks 0, 1, 2, 4, 6, 8, and 11. The genotypes of the ALDH2 polymorphism were determined using polymerase chain reactions plus restriction fragment length polymorphism analysis. A generalized estimating equation was used to analyze the effects of ALDH2 polymorphism on the clinical performance of DM. Results: PANSS and SANS scores were significantly lower in both groups after 11 weeks of treatment. SANS total scores were significantly lower in the RISP + DM group in patients with the ALDH2 *2*2 genotype. Conclusions: RISP plus add-on DM treatment reduced negative schizophrenia symptoms in patients with the ALDH2 polymorphism. Graphical abstract: Highlights: Anti-inflammatory and neurotrophic agents may benefit treatment of schizophrenia. Efficacy of dextromethorphan for negative symptoms related to neuroprotection. The ALDH2 polymorphism may moderate improvement of negative symptoms. The ALDH2 *2*2 genotype predicts better response for attenuating negative symptoms.